SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMAAN PESERTA MISS INDONESIA MENGGUNAKAN METODE TOPSIS - Adil Setiawan; Rahmadani Pane (STMIK KAPUTAMA, 2019)
Miss Indonesia is a beauty contest in Indonesian organized by MNC Group. Miss Indonesian will be the representative of Indonesian or the nation's ambassador in the International contest and participate in various social actions in the regions that need to participate in providing support and assistance. The problems that occurred in the selection of Miss Indonesian participants were due to the large number of participants registering so that it required considerable time to make decisions. Therefore a good decision support system is needed so that the selection of participants becomes more optimal. In the selection of Miss Indonesian participants, a method is needed, namely the TOPSIS method is a multicriteria decision-making method. This method is one method that is widely used to resolve practical decision making. In this method, it is used so that in the reception of Miss Indonesian participants it can be better selected according to the established criteria. The final results obtained in this study are in accordance with the expected criteria.